Pengaruh gaya kepemimpinan dan disiplin kerja terhadap kinerja karyawan di SMAN Olahraga - Dinda Tri Hapsari; Agung Dwi Nugroho (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This study aims to analyze the influence of leadership style and work discipline on employee performance at SMAN Olahraga. This research uses a quantitative method with data collection techniques through questionnaires distributed to all employees. Data analysis was conducted using multiple linear regression. The results show that leadership style significantly affects employee performance. Additionally, work discipline also has a positive and significant impact on employee performance. These findings indicate that improving the quality of leadership style and the implementation of good work discipline can enhance employee performance at SMAN Olahraga. Therefore, it is recommended that the school management focus on developing effective leadership styles and consistent application of work discipline.